MANUSIA DALAM PRESPEKTIF FILSAFAT (ISLAMIDA Journal of Islamic Studies, 2023)
The purpose of this article is to discuss humans in a philosophical perspective. The type of research is literature with documentation data collection methods, and the analysis used is content analysis. The results of the study state that humans are given the freedom to endeavor to develop potential tools and basic human potentials. However, growth and development cannot be separated from certain limits, namely the existence of definite and permanent laws governing nature, laws that control objects and human society itself, which are not subject to and do not depend on human will. Based on the explanation of the conception of man based on philosophy, raises the problem of the human dimension in the perspective of philosophy, this writing aims to find the conception of man as a whole in the philosophical review. Humans in the perspective of philosophy are also called homo sapiens, homo laquen, animal rational, homo faber, zoon politicon, homo economicus, homo planemanet, homo religious and homo educandum or educable. The soul as something that stands alone, a complete substance that exists within the prison of the human physical body.